(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Fifteen fungal species representing 12 genera were found to be associated with leaf spot and anthracnose diseases of Rauvolfia serpentina (L.) Benth. ex Kurz. which were collected from different habitats of Bangladesh. Fungi were isolated following ‘tissue planting’ and ‘blotter’ method. The isolated fungi were Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link ex Fr., A. niger van Tieghm, Colletotrichum gloeosporioides (Penz.) Sacc., Curvularia lunata (Wakker) Boedijn, Fusarium sp.1. Fusarium sp. 2, Macrophoma sp., Nigrospora sphaerica (Sacc.) Mason, Penicillium digitatum Saccardo, Penicillium italicum Whemer, Pestalotiopsis guepinii (Desm.) Stay, Pseudocercospora libenbergii (Syd.) Deighton, Rhizopus stolonifera Vuillemin. Toney, Trichoderma viride Pers. During the present investigation, Pseudocercospora libenbergii is a new record for Bangladesh. Bangladesh J. Plant Taxon. 27(1): 129-136, 2020 (June)